The influence of TQM practices on supply chain collaboration: a proposed model for the service industry - Darmawan, Nathan*; Sim, Jia Jia; Arumugam, Veeri; Chow, Kim Wai (InderScience, 2011)
This study proposes a research framework of Total Quality Management (TQM) practices towards the supply chain collaboration level. The proposed model is based on the extensive literature review; this study develops a model of TQM practices that influence the supply chain collaboration level. The findings from this study would provide a basis for developing an advanced model of TQM towards the supply chain collaboration level. The organisations that would like to implement supply chain collaboration will be able to make managerial decision based on the TQM practices from this research. This study also makes a significant contribution by developing a model of TQM and supply chain collaboration in service industry. Furthermore, the organisations could use this framework to conduct a pre-test baseline measurement and periodically assess the effect of TQM practices.